2012
DOI: 10.1080/14786419.2011.561207
|View full text |Cite
|
Sign up to set email alerts
|

Improved antioxidant activity of BKOS Thai jasmine rice

Abstract: Thai jasmine rice (Oryza sativa L. cv. KDML105) is highly valued due to its subtle aroma, robust seed characteristics and high nutritional quality. Lowenergy ion-beam bombardment was chosen to improve the quality of jasmine rice by mutation induction. One mutated variety, named BKOS, was found to exhibit a deep purple colour due to an increased accumulation of anthocyanin. The total phenolic content and antioxidant activities of cooked and uncooked rice extracts were compared with KDML105, BKOS and other rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Numerous mutant rice lines have been produced, including the Thai jasmine rice in which the anthocyanin concentration was enhanced to give blue color by the bombardment of ion-beam [50]. BKOS jasmine rice variety extracts from the mutant strain that enhanced the antioxidant activity and had high phenol content [51]. The mutant lines of low phytic acid (LPA) were produced by using physical and chemical mutagenesis from the Japonica rice and Indica rice species because phytic acid is usually recognized as an antinutritional factor [52].…”
Section: Mutation Mapping and Mutagenesis Techniques: Triggers The Nu...mentioning
confidence: 99%
“…Numerous mutant rice lines have been produced, including the Thai jasmine rice in which the anthocyanin concentration was enhanced to give blue color by the bombardment of ion-beam [50]. BKOS jasmine rice variety extracts from the mutant strain that enhanced the antioxidant activity and had high phenol content [51]. The mutant lines of low phytic acid (LPA) were produced by using physical and chemical mutagenesis from the Japonica rice and Indica rice species because phytic acid is usually recognized as an antinutritional factor [52].…”
Section: Mutation Mapping and Mutagenesis Techniques: Triggers The Nu...mentioning
confidence: 99%
“…The appearances of BKOS6 plant and its pigmented organs were shown in Figure 7. The improved characteristics of BKOS plant include: 1) anthocyanin accumulation in various tissues, especially in pericarp, which has been proven to raise the antioxidant properties of rice grain [5] and might increase resistance to blast disease of rice plant [30]; 2) semi-dwarf character, which can be more resistance against lodging and increased responsiveness to nitrogen fertilizer [31]; 3) photoperiod-insensitivity, which can promote flowering with a slightly response to photoperiod; and 4) early flowering character, which can induce early maturing. This developed variety may fit into the multiple cropping system characteristics of progressive agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…The study of its improved antioxidant properties showed the increase of total phenolic content and antioxidant activities of BKOS6 rice extracts when compared with those of KDML 105 and other tested rice extracts. Moreover, it was found that there was no significant difference between the antioxidant properties of the cooked and uncooked BKOS6 rice extracts [5]. As the consumers become more health conscious and more aware of the benefits of functional foods, diets containing bioactive compounds such as antioxidants have received greater attention.…”
Section: Introductionmentioning
confidence: 99%
“…O. sativa cv. KDML 105, or Thai jasmine rice, is known as one of the highest quality rice varieties in Thailand (Semsang et al, 2012). In addition, various parts of the rice, such as seeds, paddy, leaves, roots, rice stalks and boiling milk-like water, are used as Thai herbs to treat diseases.…”
Section: Introductionmentioning
confidence: 99%